Of mice and men: converging on a common molecular understanding of osteoarthritis - Vincent, TL (Elsevier, 2020)
Despite an increasing burden of osteoarthritis in developed societies, target discovery has been slow and there are currently no approved disease-modifying osteoarthritis drugs. This lack of progress is due in part to a series of misconceptions over the years: that osteoarthritis is an inevitable consequence of ageing, that damaged articular cartilage cannot heal itself, and that osteoarthritis is driven by synovial inflammation similar to that seen in rheumatoid arthritis. Molecular interrogation of disease through ex-vivo tissue analysis, in-vitro studies, and preclinical models have radically reshaped the knowledge landscape. Inflammation in osteoarthritis appears to be distinct from that seen in rheumatoid arthritis. Recent randomised controlled trials, using treatments repurposed from rheumatoid arthritis, have largely been unsuccessful. Genome-wide studies point to defects in repair pathways, which accords well with recent promise using growth factor therapies or Wnt pathway antagonism. Nerve growth factor has emerged as a robust target in osteoarthritis pain in phase 2-3 trials. These studies, both positive and negative, align well with those in preclinical surgical models of osteoarthritis, indicating that pathogenic mechanisms identified in mice can lead researchers to valid human targets. Several novel candidate pathways are emerging from preclinical studies that offer hope of future translational impact. Enhancing trust between industry, basic, and clinical scientists will optimise our collective chance of success.